Cost Analysis of Renal Calculi Case Detection using Ultrasonography as Screening method - Kessomboon, Pattapong; Kessomboon, Nusaraporn; Premgamone, Amorn (Srinagarind Medical Journal, 2013)
ABSTRACT OBJECTIVE : The objective of the study is to investigate the unit cost of the mobile renal calculi case detection project of the Faculty of medicine Khon Kaen University during September 1993 to June 1995. METHOD : This was a descriptive study. Data was collected retrospectively from routine records of the project expenditure and from records of observation on all activities. A mobile team comprises two trained general practitioners, a nurse, two assistants and two drivers using two trained general practitioners. A nurse, two assistants and two drivers using two ultrasounds, THOSHIBA SAL 326 linear probe 3.5 Mhz as the screening method. Costing method includes 1) Identification of screening activities involved 2) Identification of input resources in terms of capital cost and recurrent cost 3) Cost allocation to each activity and resources utilized 4) Calculation of unit cost RESULTS : The findings reveal that were 28,440 people screened and 2,617 renal calculi cases were detected. Cost per person screened was 71.34 Baht and cost per renal calculi case detected was 775.36 Baht. Labour cost was the highest component (67.03%) of the total cost. DISCUSSION : The ingestions suggest that the project could reduce the cost by using special trained mon – MD personnels, ultrasonographer, instead of MD personnels.